Dilip Kumar : The Substance and the Shadow An Autobiography - Nayar, Udayatara; As Narrated to Nayar, Udayatara (New Delhi, India Hay House India, 2016)
Autobiography of a Hindi motion picture actor.
Includes Index and Colored Illustrations
Keywords: Motion picture actors and actresses -- India -- Biography